Análisis, diseño e implementación de un sistema para el control y medición de cumplimientos de procedimientos operativos en una industria sice - Armijos F., Yessica María (2011)
Taking control of the training of corporate procedures to employees has become industries looking for measurement tools that could achieve the level of compliance, responsibility to comply with training to main objectives of this proposed system is to assist users in planning the training that must meet each of the employees as well as controlling and monitoring In this project we present a detailed review of key aspects related to the design, imp an application that performs the automated control and monitoring of training to be met by each employee in a period of time.